The Change of Oribatida Mite (Acari: Oribatida) Community Structure Follow Four Types of Soil in the Red River Delta, Vietnam - Hien, Lai Thu; Duyen, Do Thi; Manh, Vu Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4DO - 10.25073/2588-1140/vnunst.4492, 2017)
Recorded are 59 oribatida species belong to 34 genus, 20 families. In the comparision with Vu Quang Manh (2013), there are 38 species were first recorded in the reseach region, 15 species are new for the Vietnamese fauna (Vu Quang Manh, 2013). The species number in different soil types oscillated from 16 species to 26 species . A remark can be made after analysing 4 oribatida communities is that all the three oribatida communities in the group of alluvial soil are more diverse and more stable than yellow-red hummus on the mountains. There may be a specific community formed in coastal saline-acid soil. This community is a complex of species adapt to saline-acid soil, so it is not diverse in the number of species but is very stable. The result shown that soil type is in the close relationship to the oribatida community structure. Therefore oribatida can be used as a bioindicator of soil quality and proposed as a means for sustainable management of soil ecosysterm.